The Influence Of The Drill Method On Futsal Passing Technique Skills Using The Inside Of The Foot - Setyawan, Dicky Budhi (Sport Pedagogy Journal, 2024)
The purpose of this paper is to measure futsal passing skills using the drill method on a wall target. In group division, they were divided into two groups with 13 experimental students and 12 play method students. The result data obtained from the pre-test contained 3 (23%) students with adequate assessment criteria, and 10 (77%) students with inadequate assessment criteria. The increase occurred after being given the drilling method treatment on the wall target, and data obtained from post-test observations showed that there were 8 (61.5%) students who achieved the adequate assessment criteria and 5 (38.5%) students who achieved the good assessment criteria. The results of the normality test in the experimental group show that Ho is accepted, because calculated X2 X2 table. And the Homogeneity Test proves F count F table, so it can be said that the population is a homogeneous population. This research was said to be successful because students experienced progress as a result of applying the drill method treatment to the wall target.